2014
DOI: 10.1053/j.ajkd.2013.10.062
|View full text |Cite
|
Sign up to set email alerts
|

CKD of Unknown Origin in Central America: The Case for a Mesoamerican Nephropathy

Abstract: An epidemic of chronic kidney disease of unknown origin has emerged in the last decade in Central America and has been named Mesoamerican nephropathy. This form of chronic kidney disease is present primarily in young male agricultural workers from communities along the Pacific coast, especially workers in the sugarcane fields. In general, these men have a history of manual labor under very hot conditions in agricultural fields. Clinically, they usually present with normal or mildly elevated systemic blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
285
1
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(310 citation statements)
references
References 36 publications
6
285
1
18
Order By: Relevance
“…Subsequently, this disease pattern, which was similar to that of Balkan Endemic Nephropathy (9), was reported in other countries, including Nicaragua, Costa Rica, and Sri Lanka (6,(10)(11)(12), and its prevalence is now as high as 16% in some of these areas (13). In El Salvador, ESRD that is largely attributable to CKDu has become the leading cause of hospital deaths (8), and in Sri Lanka, nearly 4% of the national health care budget is now spent on treating CKDu (14,15).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Subsequently, this disease pattern, which was similar to that of Balkan Endemic Nephropathy (9), was reported in other countries, including Nicaragua, Costa Rica, and Sri Lanka (6,(10)(11)(12), and its prevalence is now as high as 16% in some of these areas (13). In El Salvador, ESRD that is largely attributable to CKDu has become the leading cause of hospital deaths (8), and in Sri Lanka, nearly 4% of the national health care budget is now spent on treating CKDu (14,15).…”
Section: Introductionsupporting
confidence: 69%
“…In our review, only two studies from Sri Lanka and two studies from Central America reported a significant association between agrochemical use and CKDu. Agrochemical use was not reported in studies from other regions, suggesting the possibility of a distinct etiology for CKD in agricultural communities in CKDu-endemic regions (6,(11)(12)(13)(14). These findings may reflect variation in the regional exposures being studied as well as difficulties in defining and quantifying agrochemical exposure, but they also highlight the need for more conclusive epidemiologic studies examining causation, particularly in agricultural communities in CKDu-endemic regions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies from Central America have reported a new kidney disease Mesoamerican nephropathy which primarily affects agricultural communities especially in the sugarcane fields. 1,5,6 It was reported to present with mild proteinuria and asymptomatic progressive kidney failure. Kidney biopsies showed chronic tubulointerstitital disease with secondary glomerulosclerosis and some signs of glomerular ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested recurrent dehydration related to manual labor under very hot conditions in agricultural fields, possibly exacerbated by NSAIDs or other toxins as a likely cause. 6 Studies from Sri Lanka and India have also reported outbreaks of CKD occurring among workers in the rice paddies. They reported that CKDu (CKD of unknown etiology) had a point prevalence ranging from 2-16% among those aged >18 years.…”
Section: Discussionmentioning
confidence: 99%